Concurrent use of aspirin with osimertinib is associated with improved survival in advanced EGFR-mutant non-small cell lung cancer. (November 2020) - Liu, Xiaoke; Hong, Lingzhi; Nilsson, Monique; Hubert, Shawna Marie; Wu, Shuhong; Rinsurongkawong, Waree; Lewis, Jeffery; Spelman, Amy; Roth, Jack; Swisher, Steven; He, Yong; Jack Lee, J.; et al.
Highlights: Concurrent aspirin use with osimertinib in EGFR -mutant NSCLC patients was associated with improved PFS. The benefit is independent of lines of therapy, CNS metastasis, EGFR mutation type, TP53 status, PD-L1 status, age or gender. With aspirin use, the progression-free survival in L858R patients are similar to the EGFR 19Del patients. Abstract: Background: Osimertinib is the treatment of choice for advanced EGFR -mutant non-small cell lung cancer (NSCLC). However, novel strategies to improve the duration of disease control are still urgently needed. Aspirin has been shown to decrease cancer incidence and improve outcomes in various malignancies. Therefore, we evaluated a cohort of patients who received osimertinib with or without concurrent use of aspirin to assess whether the addition of aspirin may lead to improved clinical outcomes. Methods: MD Anderson Cancer Center GEMINI database was retrospectively queried for EGFR -mutant NSCLC patients who received osimertinib with or without concurrent use of aspirin for progression-free survival (PFS) and overall survival (OS). Results: A total of 365 patients were identified including 77 which had concurrent use of aspirin. Patients in the aspirin-osimertinib group had significantly improved PFS (21.3 vs 11.6 months; HR, 0.52; 95 % CI, 0.38−0.70) and OS (Not reached vs 32.3 months; HR, 0.56; 95 % CI, 0.35−0.91) compared to osimertinib group. In subgroup analyses, the aspirin-associated PFS benefit was observed in patients with and without central nervous system (CNS) metastases, as well as in osimertinib first-line setting and in subsequent line setting. The median PFS in EGFR 19Del patients was longer than EGFR L858R patients with osimertinib, and when aspirin was added, the median PFS significantly improved in both groups regardless of lines of therapy. The benefit from aspirin was independent of age, gender, TP53 mutational status, or PD-L1 positivity. Conclusion: Concurrent aspirin use with osimertinib in EGFR -mutant NSCLC patients was associated with improved survival, regardless of lines of therapy, CNS metastatic status, EGFR mutation type, age, gender, TP53, and PD-L1 status.